Using chemical biology to assess and modulate mitochondria: progress and challenges. Issue 2 (6th April 2017) - Logan, Angela; Murphy, Michael P.
Abstract : Our understanding of the role of mitochondria in biomedical sciences has expanded considerably over the past decade. In addition to their well-known metabolic roles, mitochondrial are also central to signalling for various processes through the generation of signals such as ROS and metabolites that affect cellular homeostasis, as well as other processes such as cell death and inflammation. Thus, mitochondrial function and dysfunction are central to the health and fate of the cell. Consequently, there is considerable interest in better understanding and assessing the many roles of mitochondria. Furthermore, there is also a growing realization that mitochondrial are a promising drug target in a wide range of pathologies. The application of interdisciplinary approaches at the interface between chemistry and biology are opening up new opportunities to understand mitochondrial function and in assessing the role of the organelle in biology. This work and the experience thus gained are leading to the development of new classes of therapies. Here, we overview the progress that has been made to date on exploring the chemical biology of the organelle and then focus on future challenges and opportunities that face this rapidly developing field.